Screening for Hearing Impairment Using hearWHO Application among College Students of a Tertiary Care Hospital of North Kerala - A Cross-Sectional Study - Swathi Chalil; Shilpa Karir; Remya Ramachandran; Sandeep Sreedhar; Shakhy Vati; Deepak Raj PV (National Journal of Community Medicine, 2026)
Background: Rising use of personal listening devices and prolonged exposure to environmental noise have made hearing impairment an emerging concern among young adults, including college students. Data on its burden in this group, particularly using mobile-based screening tools, remain limited in Kerala. Objectives: To determine the prevalence and associated factors of likely hearing impairment among undiagnosed college students at a tertiary care hospital in North Kerala, and to confirm hearing loss among screen-positive individuals using Pure Tone Audiometry (PTA). Methods: This cross-sectional study enrolled 307 students from MBBS, nursing, and allied health science programs. Hearing status was assessed using the WHO-validated hearWHO application, with scores below 50 triggering referrals for ENT evaluation and PTA. Associated factors were analyzed using Chi-square tests and logistic regression. Results: Participants had a mean age of 21.26 ± 1.6 years, with females comprising 76.2% of the sample. Screening identified 5.9% with likely hearing impairment, 83.7% requiring monitoring (scores 50–75), and 10.4% with good hearing. PTA confirmed hearing loss in 1.6% (n=5) of participants. Earphone use exceeding recommended volume levels was common. Conclusion: These findings highlight a measurable burden of hearing impairment among college students, underscoring the need for periodic screening, particularly for those in the monitoring range, and awareness initiatives promoting safer listening practices and app-based screening tools.